THE EFFECT OF HUMAN RESOURCE COMPETENCIES, IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARDS, FINANCIAL ACCOUNTING SYSTEMS, INTERNAL CONTROL SYSTEMS AND UTILIZATION OF INFORMATION TECHNOLOGY ON THE QUALITY OF LOCAL GOVERNMENT FINANCIAL REPORTS - Putri, Silvy Agustina Putri; Rina Trisnawati (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this research is to examine the influence of human resource competency, implementation of government accounting standards, financial accounting systems, internal control systems, and utilization of information technology on the quality of local government financial reports. This research is an empirical study conducted on Regional Work Units (SKPD) in Ngawi Regency using a quantitative approach. The type of data used is primary data, collected through questionnaire distribution to respondents. The respondents in this study are employees in the financial departments of SKPD in Ngawi Regency, with a sample size of 54 people. The sampling technique was conducted using non-probability sampling method. The obtained data was then processed and analyzed using SmartPLS 3 application. The research results show that human resource competency, implementation of government accounting standards, and utilization of information technology do not influence the quality of local government financial reports. Meanwhile, financial accounting systems and internal control systems are proven to have an influence on the quality of local government financial reports.